Design and development of micro EDM using micro actuator tool feed system - Thinesh Chander, Sawalingam (2010)
This project aims in revealing varieties of methods in tool feed control for Micro electric discharge machining (EDM) process with new advanced technology achieved. Although Micro EDM usage is essential in manufacturing sector but the gap phenomena still remains complicated and unstable. Recent research improves the gap control problem with latest technology such as servomechanism, fuzzy logic, Piezoelectric transducer (PZT), ultrasonic vibration and many more. PZT tool feed control system is used in this project as the main system to prevent any adhesion and to reduce tool wear. This project also aims in discussing factors influencing tool wear and new tool materials in Micro EDM. Tool wear prevention in EDM is essential because quality and precision of the product machined by EDM depends on the tool wear. If the tool wear is high, the product machined depth will be inaccurate with low surface quality. In future prospect, Micro EDM should be equipped with self learning and user friendly utilities for mass production usage. Future Micro EDM will be a package of integrated self learning and fast production machine.